Shift Kerja Dan Beban Kerja Berpengaruh Terhadap Terjadinya Kelelahan Kerja Perawat Di Ruang Rawat Di Rumah Sakit Pemerintah - Rusdi Rusdi; Bambang Edi Warsito (Jurnal Manajemen Keperawatan, 2014)
The Effects of Work Shift and Workload towards the Occurrence of Nurses Work Fatigue in Inpatient Ward of Governence Hospital. Introduction: Nurses work fatigue is an important problem in any industrial process, including nursing services industrial sector. Nurses work fatigue can lead to work accidents to patients and nurses themselves. Heavy workload and patterns of non-standard work shift can lead to work fatigue to nurses who work in shifts. Methods: This research aims to determine the effect of work shift and workload on nurses work fatigue. The kind of this research is an analytical survey with cross sectional design. The subjects of this research are 30 respondents. Each respondent was measured its fatigue before and after working. Work shift was measured by using a standard checklist sheet of work shift,workload was measured by using the daily log and work fatigue was measured by using a Raction meter Lakasidaya L 77. Result: Data analysis was performed by using bivariate analysis with Chi-Square test to determine the effect of the independent variables on the dependent variable and multivariate analysis by using logistic regression analysis with Backward LR method.The results of bivariate analysis of the independent variable that influences on the dependent variable (nurses work fatigue) are: morning work shift (p value = 0.030), evining work shift )p value = 0,038), night work shift (p value = 0.042), morning workload (p value = 0.014), evening workload (p value = 0.042) and night workloads (p value = 0.004). On the multivariate analysis, the variables that influence are morning work shift (OR = 0.082), night work shift (OR = 0.053), night workload (OR = 0.028). Recommendation: For Nurse manager, the result this research can be input for humen resource policy in shift system must gain for work shift and work load standard.